Psychedelics for Brain Injury: A Mini-Review - Khan, Mia; Carter, Gregory T.; Aggarwal, Sunil K.; Holland, Julie (Frontiers in Neurology, 2021)
Objective: Brain injury due to stroke and traumatic brain injury (TBI) is one of the leading causes of disability. Even after engaging in an appropriate rehabilitation program, nearly half of patients with severe traumatic brain injury requiring hospitalization will be left with chronic severe disability. Despite decades of investigation, pharmacologic treatment of brain injury is still a field in its infancy, suffering from a lack of consistently proven drug regimens. Recent clinical trials have begun into the use of psychedelic therapeutics for treatment of brain injury. This brief review aims to summarize the current state of the science’s relevance to neurorehabilitation. Methods: Scoping review of all studies published related to psychedelic therapeutics and brain injury. Results: Recent in vitro, in vivo, and case report studies suggest psychedelic pharmacotherapies may radically alter the future of brain injury treatment through modulation of neuroinflammation, neuroplasticity, hippocampal neurogenesis, and brain complexity. Conclusions: Historical data on the safety of these substances could serve in effect as phase 0 and phase I studies. N,N-Dimethyltryptamine is currently undergoing clinical trials for treatment of stroke. Further phase II trials will illuminate how these promising drugs may treat brain injury, particularly TBI and reperfusion injury from stroke.